2013
DOI: 10.1097/bot.0b013e3182519492
|View full text |Cite
|
Sign up to set email alerts
|

Low-Intensity Pulsed Ultrasound Enhances BMP-7-Induced Osteogenic Differentiation of Human Fracture Hematoma-Derived Progenitor Cells In Vitro

Abstract: These findings demonstrated for the first time the significant effect of LIPUS on the osteogenic differentiation of HCs in the presence of BMP-7. This study may provide significant evidence for the clinical combined application of BMP-7 and LIPUS for the treatment of acute bone fractures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 30 publications
1
14
0
Order By: Relevance
“…The Institutional Review Board of Kobe University Hospital approved this study and informed consent was obtained from all patients. Human fracture HCs were isolated and cultured as previously described (Oe et al, 2007;Hasegawa et al, 2009;Lee et al, 2013). Briefly, haematoma at the fracture site was harvested and minced into small pieces with growth medium [GM; α-modified minimum essential medium (α-MEM; Sigma, St. Louis, MO, USA) containing 10% heat-inactivated fetal bovine serum (FBS; Sigma), 2 mM L-glutamine (Gibco, Carlsbad, CA, USA) and antibiotics] in a culture dish.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The Institutional Review Board of Kobe University Hospital approved this study and informed consent was obtained from all patients. Human fracture HCs were isolated and cultured as previously described (Oe et al, 2007;Hasegawa et al, 2009;Lee et al, 2013). Briefly, haematoma at the fracture site was harvested and minced into small pieces with growth medium [GM; α-modified minimum essential medium (α-MEM; Sigma, St. Louis, MO, USA) containing 10% heat-inactivated fetal bovine serum (FBS; Sigma), 2 mM L-glutamine (Gibco, Carlsbad, CA, USA) and antibiotics] in a culture dish.…”
Section: Methodsmentioning
confidence: 99%
“…HCs (7 × 10 4 cells/well) were seeded into a six-well plate and were cultured for 20 days in an osteogenic medium consisting of GM supplemented with 10 mM β-glycerophosphate (Sigma) and 50 μg/ml ascorbic acid (Wako, Osaka, Japan) (Hasegawa et al, 2007;Lee et al, 2013). For chondrogenic differentiation, a pellet culture was performed for three-dimensional (3D) culture.…”
Section: Osteogenic and Chondrogenic Inductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In differentiating murine osteoblasts, LIPUS has been found to enhance RANKL gene expression 10-fold compared to unstimulated controls after 3 weeks of LIPUS treatment [84]. It was also reported that LIPUS combined with growth factors such as calcium-regulating hormones, 1,25-dihydroxyvitamin D3 (1,25-(OH)2D3) [86], BMP2 [87], or BMP7 [88], can stimulate bone repair.…”
Section: Physical Stimulation For Bone Regeneration and Fracture Healingmentioning
confidence: 99%
“…We used a low-intensity pulsed US exposure device (Teijin Pharma Ltd, Tokyo, Japan) that was adapted for use with a 6-well culture plate in the in vitro experiments ( Figure 1). 17,[21][22][23] The thickness of the plate bottom was 1.5 mm. The volume of growth medium in each well was 2 mL.…”
Section: Low-intensity Pulsed Us Treatmentmentioning
confidence: 99%